A study on the emerging markets to compare the performances between conventional and Islamic stock markets due to the emergence of Covid-19 pandemic: an empirical analysis based on volatility, efficiency and integration - Hossain, Fyrooz Maisha (2021)
This study aims to investigate whether emerging Islamic stock markets perform better than their conventional counterparts during-COVID-19 pandemic relative to pre-COVID-19 time period, by analyzing the time-varying changes in volatility, efficiency and integration. The main purpose of this study is to analyze how the emerging stock markets are reacting for better policy recommendations and investment strategies. To investigate the objectives, this study employs a four-step process. (1) The wavelet decomposition to fragment data in shorter and longer horizon, (2) EGARCH to measure volatility, (3) the multifractal de-trend fluctuation analysis (MF-DFA) for efficiency ranking, (4) MGARCH to measure integration. The overall study finds that the performance for both emerging conventional and their Islamic counterparts deteriorate relative to the pre-COVID-19 pandemic, but the Islamic stock markets perform better during-COVID-19 pandemic in comparison to their conventional counterparts. Results provide evidence of higher efficiency and lower integration but higher volatility which results in higher return to the investors of the Islamic stock markets. Implying to the Islamic stock markets shari’ah compliance laws and their unique characteristics, the under-diversification causes higher volatility and lower integration in shorter horizons (an inverse relationship is observed in the longer horizon). But good governance and discloser mechanism allows for adjustments to speculative activities leading to higher efficiency in the longer horizon than their conventional counterparts. Further, to test the robustness, the study employs three robustness checks. (1) Fragments the data into shorter and longer horizon, (2) uses standard deviation to measure volatility, (3) employs pooled OLS regression, and in general, results held. Therefore, the interconnected relationship is also observed between these three parameters.